THE EFFECT OF PRE-STORAG INCUBATION STORAGE ON CHICK QUALITY OF BROILER BREEDER ( ROSS 308 ) - AL-Samrai, Ezat KH.; AL-Dhanki, ZIAD T. (Diyala Agricultural Sciences Journal, 2013)
This study were conducted in AL-Furat commercial Hatchery from 18/12/2010 to 3/1/2011. A total of 1080 hatching eggs were collected from broiler breeders (ROSS 308) commercial farm at age of 364 days (52 wk), the eggs were randomly distributed into 9 treatment groups (120 eggs/treatment). The pre-incubation process were done for 0, 6 and 12 hours then the eggs were stored for 4 days in the 1st, 2nd and 3rd treatment, and for 7 days in the 4th, 5th and 6th treatment, and for 14 days in the 7th , 8th and 9th treatment respectively. The pre-incubation process were carried in temperature of 37.5 C (99.5 F) and RH of 55% (29.8 C or 85.6 F dry bulb temperature), and the storage condition were 18 C and RH of 55-60%. The results showed no significant differences for egg weight and the process of storage for a period of 7 days without cuddling advance led to outweigh the weight of chicks hatched ,weight ratio chick to egg weight, as more than the length of and specifications Tona quality of the chicks in chicks hatched of eggs stock for 4 days after his lap for 12 hours, but the body mass was significantly superior in chicks inventory of eggs for 12 hours after his lap in advance for a period of 6 hours